Effects of a neuroscience-based instructional guide on college student learning - Barboza Arenas, Luis Andrés (2022)
The article aims to demonstrate the impact of neuroscience as an instructional strategy on student learning. This was an experimental research with a pre-experimental design that used a sample of 60 students on the Mathematics 1.0 course of the first cycle of the Continental University in the Academic period II - 2021. Significant contrasts were found between the results obtained before and after the application of the designed instructional guide, since the T value obtained is related with a significance level lower than 0.01, confirming the research hypothesis. When evaluating the effect of the application of the instructional guide with neuroscience as a strategy, it is shown to favorably affect the learning of students of the Mathematics 1.0 course of the first cycle of the Continental University, strengthening the entire learning process so that these can become meaningful. Therefore, it is recommended to continue implementing the instructional guide in all higher education courses without being limited to a single course as in the present study, as well as continue researching on the subject with larger samples.